Risk Factors Associated with the Prevalence of Diarrhea among Toddlers in the Catchment Area of Namang Primary Health Center - Febrio Aliansah; Indri Puji Lestari (Genius Journal, 2026)
Objective:Diarrhea in children is a condition in which children experience an increase in the number of bowel movements due to a digestive tract disorder. The stool consistency is watery and liquid (contains a lot of fluid) and usually occurs more than three times in 24 hours. The purpose of this study was to determine the relationship between nutritional status, diet, and knowledge and the incidence of diarrhea in toddlers in the Namang Community Health Center work area in 20 Method: This study used a cross-sectional design with independent variables (nutritional status, diet, and knowledge) and dependent variable (diarrhea incidence). The population size in this study was 375 people, and a sample of 87 people was calculated using random sampling Result: The results of the study, using the Chi-Square statistical test, yielded a p-value of 0.000 < 0.05 for nutritional status, 0.000 < 0.05 for dietary patterns, and 0.000 < 0.05 for knowledge. This indicates a significant relationship between nutritional status, dietary patterns, and knowledge and the incidence of diarrhea in toddlers in the Namang Community Health Center work area in 2025. Conclusion: The recommendations in this study are expected to serve as evaluation material for the importance of support from health workers in the diarrhea treatment process. This should be a focus for health institutions in designing broader work programs that will impact recovery, particularly diarrhea in toddlers